GAMBARAN PEMERIKSAAN Trichomonas vaginalis PADA URIN PEKERJA SEKS KOMERSIAL (PSK) DI KAWASAN BOKER JAKARTA TIMUR - Erna Tristiyanti; Adelia Febriyossa (Jurnal Medical Laboratory, 2022)
ABSTRACT Commercial Sex Workers (PSK) can be a source of livelihood for some people. PSK is one of the lucrative alternative jobs compared to being unemployed because it is easy to do and does not need to be difficult. However, working as a prostitute is known to be at risk of experiencing Sexually Transmitted Infections (IMS) caused by microorganism infections, which have an impact on the health of reproductive organs. One of the causes of STIs is infection with the parasite Trichomonas vaginalis. The parasite T. vaginalis is a protozoa group of microorganisms that can cause vaginal discharge and inflammation of the vagina. This study aims to determine the description of T. vaginalis in the urine of sex workers in the Boker area of ​​East Jakarta. The research method used a qualitative analysis conducted at the Gunung Sahari Citra Laboratory in March-May 2020. The results obtained from 50 sex workers, 11 people (22%) were infected with the protozoa T. vaginalis with the most sexual characteristics of sex workers based on age, namely 26-35. years as many as 27 people (54%), the most being SMP as many as 22 people (44%), the length of being a prostitute is 7-12 months, namely 18 people (36%), the highest number of customers is 3 people per day as many as 14 people (30%) , the most marital status was ever married as many as 23 people (46%), the most from the island of Java as many as 41 people (82%), customers PSK using condoms as many as 37 people (74%), PSK who do not use vaginal antiseptic every day as many as 32 people (22%), sex workers often experience vaginal discharge as many as 32 people (64%) and experience itching and heat as many as 6 people (12%) while the characteristics of the level of knowledge of sex workers about the dangers of infection with T. vaginalis are mostly 8 people (16%). Keywords: Sex Workers, Trichomonas vaginalis, Urine ABSTRAK Pekerja Seks Komersial (PSK) dapat menjadi salah satu mata pencaharian bagi sebagian orang. PSK menjadi salah satu alternatif lahan pekerjaan yang menggiurkan dibandingkan menjadi pengangguran dikarenakan mudah untuk dilakukan dan tidak perlu bersusah payah. Namun, pekerjaan menjadi PSK diketahui beresiko mengalami Infeksi Menular Seksual (IMS) yang disebabkan infeksi mikroorganisme sehingga berdampak pada penurunan kesehatan organ reproduksi. Salah satu penyebab IMS adalah infeksi parasit Trichomonas vaginalis. Parasit T. vaginalis merupakan mikroorganisme kelompok protozoa yang dapat menyebabkan keputihan dan radang vagina. Penelitian ini bertujuan mengetahui gambaran T. vaginalis pada urin PSK di Kawasan Boker Jakarta Timur. Metode penelitian menggunakan analisa kualitatif yang dilakukan di Laboratorium Gunung Sahari Citra pada bulan Maret-Mei 2020. Hasil penelitian didapatkan dari 50 orang PSK sebanyak 11 orang (22%) terinfeksi protozoa T. vaginalis dengan karakteristik perilaku seks PSK berdasarkan usia terbanyak yaitu 26-35 tahun sebanyak 27 orang (54%), terbanyak yaitu SMP sebanyak 22 orang (44%), lama menjadi PSK adalah 7-12 bulan yaitu 18 orang (36%), jumlah pelanggan terbanyak yaitu 3 orang perhari sebanyak 14 orang (30%), status pernikahan terbanyak yaitu pernah menikah sebanyak 23 orang (46%), asal PSK terbanyak dari pulau Jawa sebanyak 41 orang (82%), pelanggan PSK menggunakan kondom sebanyak 37 orang (74%), PSK yang tidak menggunakan antiseptik vagina setiap hari sebanyak 32 orang (22%), PSK sering mengalami keputihan sebanyak 32 orang (64%) dan mengalami gatal dan panas sebanyak 6 orang (12%) sedangkan karakteristik tingkat pengetahuan PSK terhadap bahaya infeksi T. vaginalis terbanyak adalah 8 orang (16%). Kata Kunci: Pekerja Seks Komersial, Trichomonas vaginalis, Urin